Differential response of terpenes and anthraquinones derivatives in Rumex dentatus and Lavandula officinalis to harsh winters across north-western Himalaya. Issue 5 (3rd March 2016) - Jan, Sumira; Kamili, Azra N.; Parray, Javid A.; Bedi, Yashbir S.
Abstract : Herbs adapted to diverse climates exhibit distinct variability to fluctuating temperatures and demonstrate various metabolic and physiological adaptations to harsh environments. In this research, Rumex dentatus L. and Lavandula officinalis L. were collected before snowfall in September–November to evaluate variability in major phytoconstituents to diverse seasonal regime. LC-MS was used for simultaneous determination of eight anthraquinone derivatives in R. dentatus, i.e. emodin, physcion, chrysophanol, physcion glucoside, endocrocin, emodin glucoside, chrysophanol glucoside and chromone derivatives and monoterpenes in L. officinalis i.e. ( Z )-β -ocimene, ( E )-β-ocimene, terpene alcohol, terpin-4-ol, acetate ester-linalyl acetate and bicyclic sesquiterpene ( E )-caryophyllene. The correlation analysis confirmed significant variation in anthraquinone glucoside and terpene content within Rumex and Lavender, respectively, and altitude was established as the determinant factor in secondary metabolism of both herbs. The study concludes the propagation of herbs in bioclimatic belts which favour accumulation of major constituents and validate their greater pharmacological activity. Abstract :